Early career teacher attrition in Australia: evidence, definition, classification and measurement. Issue 1 (April 2018) - Weldon, Paul
Scholarly articles and the Australian media claim that 30–50% of Australian teachers leave teaching within their first five years in the role. The figures are considered to be well established although some articles acknowledge that they are estimates. In reality, there is no robust Australian evidence, and figures do not agree. What evidence there is, nationally and internationally, suggests that attrition is dynamic, varies by school level and location, and is not always negative and not always due to the school environment. In the absence of Australian evidence, articles should be more cautious about figures cited, and about causation. Attention should be paid to the classification of attrition types and a typology is outlined in this article, based on the teacher supply pipeline, along with what evidence exists on teacher exits at each level. This typology may facilitate greater transparency about levels of early career teacher attrition, leading to a broader and more nuanced policy and research conversation in the area of teacher supply.